Digital Storytelling sebagai Pendekatan Inovatif dalam Pengembangan Media Pembelajaran Interaktif pada Mata Pelajaran Informatika - Ashifa, Annisa; Dewi, Ika Parma (MASALIQ, 2025)
The lack of interactive and engaging learning media in the Informatics subject has become a major obstacle in enhancing concept comprehension and learning motivation among Grade X students at SMK Negeri 6 Padang. This study aims to develop interactive learning media based on digital storytelling as an innovative solution to provide meaningful and contextual learning experiences. The media was developed using the 4D model (Define, Design, Develop, Disseminate) and utilized the Canva platform, which integrates visual, audio, and interactive elements. Validation by subject matter and media experts indicated that the media is highly suitable for use, with feasibility scores of 89% and 91.87%, respectively. A practicality test conducted on 31 students yielded an average score of 87.80%, indicating that the media is very practical and easy to use. The results demonstrate that the digital storytelling approach is effective in fostering student engagement and enhancing understanding of Informatics content. In conclusion, this learning media holds significant potential for improving the quality of Informatics instruction at vocational schools. The implications suggest that this media is suitable for further development by adding additional interactive features to enrich the learning process and expanding its application to reach students across various vocational education units.